RNA–DNA hybrid nano-materials for highly efficient and long lasting RNA interference effect. Issue 5 (20th January 2023) - Kim, Joung Sug; Park, Junghyun; Choi, Jang Hyeon; Kang, Seungjae; Park, Nokyoung
Abstract : A new RNAi approach was developed using an X-RDNA and Ri-Dgel. The nanostructured materials of dsRNA–DNA hybrids showed higher efficient and longer lasting RNA interference effect compared with conventional dsRNA. Abstract : In attempts to effectively improve RNAi function, we herein report a new RNAi approach using X-shaped RDNA and Dgel (RNA interfering DNA hydrogel, Ri-Dgel). X-shaped RDNA is a 4 branched nanostructure which was composed of three dsDNA branches and one dsRNA branch, and the structure was made by annealing partially complementary ssDNAs and chimeric RNA–DNA oligonucleotides. Ri-Dgel was synthesized through the ligation of the X-shaped RDNAs using their palindromic sticky ends. In MDCK/GFP cells transfected with 1 μM of each format of siRNA, Ri-Dgel and X-RDNA, the intensity of GFP fluorescence was significantly reduced by 65% and 56%, respectively, while dsRNA which is a conventional siRNA format showed a relatively weak reduction intensity of 7% compared with a negative control. We also observed the decreased intensity of GFP fluorescence by approximately 59% in MDA-MB-231/GFP cells transfected with 5 nM Ri-Dgel. Furthermore, the Ri-Dgel showed persistent RNAi efficiency up to 6 days from the treatment. The use of Ri-Dgel to trigger RNAi resulted in enhanced efficacy and longer duration at lower concentration compared to traditional dsRNA implying the nanostructured DNA–RNA hybrid materials have great potential as a platform technology for RNAi-based therapy.